SA-6 Foreign Objects in the Form of Nails Found Inside the Gastrim of a Mixed Breed Dog Patient Handled at Klinik Hewan Jogja - Ida Tjahajati; Adellyna Chrissandra; Anggi D Prayitno; Begum F R Aditya; E Rrarindah; L Rifiyanta; M A Candra; Sri Indah Astuti; T A Widiastuti (Hemera Zoa, 2018)
Various diseases could affect dogs, including disruptions of the gastrium caused by the presence of foreign objects. The dogs’ habit of consuming miscellaneous objects around them was the common cause for the said objects, which should not exist within their body, to be swallowed and enter the stomach. This kind of case is often found among the growing puppies of large breed dogs [1]. This report aims to reveal the case of foreign objects finding within the gastrium of a dog patient handled at Klinik Hewan Jogja. In this particular case, we found foreign objects in the form of many nails and an assortment of metal wire pieces inside the gastrium of mixed breed dog Messi.